Demographic and Social-Economic Determinants of Malnutrition among Children (0-23 Months Old) in Kenya - Mbogori, Teresia; Muriuki, James (International Journal of Child Health and Nutrition, 2021)
Objective: To identify the demographic, social, and economic determinants of malnutrition in Kenya's children aged 0-23 months. Methods: Data from the Kenya Demographic and Health Survey (KDHS), a nationally representative cross-sectional study conducted in 2014/2015, were used in this study. Data from children 0-23 months old with complete information on weight, height, age, and sex were used for analysis. Height for Age Z scores (HAZ), Weight for Height Z scores (WHZ), and BMI for age Z scores (BAZ) was determined using WHO guidelines to determine the nutritional status of the children. Chi-square statistics were used to determine the relationship between social-economic status and place of residence indicators and the nutritional status of the children. Significance was set at p <0.05. Results: Among all participating (n=7578), 22.7% were stunted (HAZ < -2), 6.2% were wasted (WHZ < -2), and 6.1% were either overweight or obese (BAZ > 2). Wasting and stunting were significantly higher in children from rural areas, poorer wealth index, and mothers with no education. In contrast, children from urban areas, the richest wealth index category, and mothers with secondary or higher education were significantly more likely to be overweight or obese. Conclusion: Current and future policies and programs to curb malnutrition in Kenya need to target specific needs of children based on their social-economic status, area of residence, and other demographic characteristics that were identified as determinants of child malnutrition instead of using a general approach.